Yellow submarine resurfaces - Lennon, John, 1940-1980.; McCartney, Paul.; Harrison, George, 1943-2001.; Wells, Bill; Moffat, Aidan; Saloman, Nick.; Gelb, Howe.; White, Jim, 1957-; Duncan, Natalie; Shelley, Pete.; Stodart, Michele; Leftwich, Benjamin Francis; et al. ([London] : Mojo, 2012)
"This bespoke MOJO compilation brings together music from Yellow Submarine's soundtrack as well as music from that same period." -- insert.
Yellow submarine (Bill Wells & Aidan Moffat) -- Hey bulldog (Bevis Frond) -- Eleanor Rigby (Howe Gelb) -- Love you to / written by George Harrison (Cornershop) -- All together now (Jim White) -- Lucy in the sky with diamonds (Natalie Duncan) -- Think for yourself / written by George Harrison (Pete Shelley) -- Sgt. Pepper's Lonely Hearts Club band (Michele Stodart) -- With a little help from my friends (Benjamin Francis Leftwich) -- Baby, you're a rich man (Wooden Wand) -- Only a northern song / written by George Harrison (Gravenhurst) -- All you need is love (Thea Gilmore) -- When I'm sixty-four (Baxter Dury) -- Nowhere man (Cornshed Sisters) -- It's all too much / written by George Harrison (My Darling Clementine).
Title from container.
All songs written by Lennon and McCartney except where noted.
"Includes 15 all new recordings by your favorite artists."
"This bespoke MOJO compilation brings together music from Yellow Submarine's soundtrack as well as music from that same period" -- insert.
"Given away free with MOJO July 2012. Not to be sold separately."
Compact disc.
Keywords: Cover versions; Motion picture music; Rock music -- 2011-2020.; Popular music -- 2011-2020.